2019
DOI: 10.1080/19768354.2019.1575904
|View full text |Cite
|
Sign up to set email alerts
|

Immune response of heterologous recombinant antigenic protein of viral hemorrhagic septicemia virus (VHSV) in mice

Abstract: Viral hemorrhagic septicemia (VHS) is an important infectious disease in fish worldwide caused by viral hemorrhagic septicemia virus (VHSV). VHSV is the causative agent of serious systemic diseases in fish, affecting a number of teleost fish species. In this study, VHSV glycoprotein (G), including its epitope, as a subunit vaccine candidate, was expressed in tobacco plant ( Nicotiana tabacum ). The recombinant gene, VHSVG, was fused to the immunoglobulin Fc fragment and extended with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 41 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…The higher purification efficiency of both antibodies might be due to the effect of the C-terminal-fused ER retention motif KDEL. Previous studies prove that mAbs were not retained in the ER in the absence of an ER retention motif [ 25 , 26 , 47 , 48 , 49 ]. They indicated that a protein fused with the KDEL motif at the C-terminal end is retained in the ER or is returned to the ER and its production levels are also improved [ 2 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The higher purification efficiency of both antibodies might be due to the effect of the C-terminal-fused ER retention motif KDEL. Previous studies prove that mAbs were not retained in the ER in the absence of an ER retention motif [ 25 , 26 , 47 , 48 , 49 ]. They indicated that a protein fused with the KDEL motif at the C-terminal end is retained in the ER or is returned to the ER and its production levels are also improved [ 2 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…They indicated that a protein fused with the KDEL motif at the C-terminal end is retained in the ER or is returned to the ER and its production levels are also improved [ 2 , 50 , 51 , 52 ]. The ER is a vast subcellular location for the accumulation of proteins that do not require the proteolytic process found in the secretory pathway of intracellular and extracellular spaces [ 23 , 24 , 25 , 26 , 28 , 53 , 54 ]. The figure of Immunoblot analysis to confirm the purified fraction of mAb 13F6-FULL from transgenic N. tabacum plants for Figure 4 A was included as a Figure S2 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To purify the plant-derived anti-HER2 VHH-FcK, 200 g of leaves were homogenized with extraction buffer (37.5 mM Tris/HCl pH 7.5, 50 mM NaCl, 15 mM ethylenediaminetetra acetic acid (EDTA) pH 8.0, 75 mM sodium citrate, and 0.2% sodium thiosulfate) and centrifuged at 9000× g for 30 min at 4 • C [34]. The supernatant was filtered using Miracloth (Biosciences, La Jolla, CA, USA).…”
Section: Plant Growth and Purificationmentioning
confidence: 99%